Perhitungan Harga Pokok Penjualan Pada Umkm Mie Ayam Bakso Nusantara - Rakhman, Arif; Maula, Kholida Atiyatul; Dewi, Marischa Aulia; Natalia, Anggi Amanda; Rani, Rani; Syahidah, Cinta Azzahara Ulla; Wahyudi, Adi Aris; Za'imuddin, Za'imuddin; Uliarta, Magdalena (Peneliti.net, 2024)
This research aims to analyze the calculation of the cost of goods sold (HPP) for Micro, Small and Medium Enterprises (MSMEs)